Professional requirements for a sociocultural animator: key competences - Mª Luisa Sarrate Capdevila; José Luis García Llamas; Gloria Perez Serrano (Sociedad Iberoamericana de Pedagogía Social, 2013)
This article comes from a project sponsored by AECID of Educational Intervention on Social contexts and it approaches a specific dimension. As they contribute to solve several problems, sociocultural professionals claim for higher recognition. Given their superior studies they have been able to open a professional specific space. Their CV nowincludes aptitudes, abilities and skills toperform a job linked to several scenarios and contexts. The goals of this research are either to identify the key competences of the sociocultural animator that contribute towork efficiently andtodetect their educational needs. A multimethodological approach has been used. A survey was made to sociocultural animators allover Spain, with a reliability of 0,930 Cronbach's alpha. Semi organized interviews were made to key informants. 376 surveys were received back. The SSP programwas used for statistical treatment for quantitative data, including variance and factorial analysis. Atlas-ti was used for qualitative data. In order toclassify theresults, competenceswere divided into three categories: methodological, planning and generic, confirming that the sociocultural workers have the monahigh degree.The factor analysis reflects that the three initially proposed working fields linked to professional performance became four with the empirical work.There is a good identification between the methodological and planning competences, while the generic is divided into: generic and transversal. A combination of them creates the professional profile, a compulsory reference source.